A Novel Cyclopentadienone and its Ruthenium and Iron Tricarbonyl Complexes. Issue 46 (23rd November 2021) - Nährig, Florian; Nunheim, Nelly; Salih, Kifah S. M.; Chung, Jae‐Yeon; Gond, Dominik; Sun, Yu; Becker, Sabine; Thiel, Werner R.
Abstract: A simple and efficient protocol allows the oxidation of the cyclopentadiene derivative 5H‐dibenzo[e, h]‐dibenzo[3, 4 : 6, 7]cyclohept[1, 2‐a]azulene (Cp C H) provide according ketone Cp C O. Comparable to the situation found for Cp C H, the bending of the four annulated six‐membered rings defines the C 2 symmetric molecular structure of Cp C O. The cyclopentadienone Cp C O readily reacts with [Ru3 (CO)12 ] and [Fe3 (CO)12 ] to generate tricarbonyl complexes of the type [(η 4 ‐Cp C O)M(CO)3 ]. In contrast to [(η 4 ‐Cp C O)Ru(CO)3 ], the tricarbonyliron(0) complex is sensitive to oxygen and moisture. Refluxing [(η 4 ‐Cp C O)Ru(CO)3 ] in isopropanol makes the hydrido‐bridged complex [((η 4 ‐Cp C O)2 H)Ru2 (CO)4 H] accessible, an analogue to Shvo's catalyst. Both ruthenium complexes and their ligand Cp C O were characterized spectroscopically and by single crystal x‐ray diffraction. The activity of [(η 4 ‐Cp C O)Ru(CO)3 ] was investigated for a series of transfer hydrogenation reactions. Abstract : The annulated cyclopentadienone ligand Cp C O provides access to ruthenium carbonyl complexes being structurally related to Shvo's catalyst. The bending of the Cp C O backbone allows the formation of rac and meso isomers. These compounds show good catalytic activity for additive‐free transfer hydrogenation and dehydrogenation reactions.